Transformações e reverberações da formação no espaço escolar : o desenho infantil enquanto norte - Faria, Alessandra Ancona de (2018)
This work discusses the transformations of school space as a result of a process of teacher training, with children’s drawing as the central element. We will analyze the approach offered to the children, considering the space of the school and its graphic representations, observing the changes of the educators’ gaze. The results show us the importance of the presence of the trainer in the school space